Aggressive intraoperative warming and postoperative pulmonary complications in elderly patients recovering from esophageal cancer surgery: sub-analysis of a randomized trial - Lu, Xiaofei; Jiang, Qiliang; Qiu, Yuwei; Tang, Wei; Sessler, Daniel I.; Wu, Jingxiang (Frontiers in Medicine, 2023)
Background Elderly patients having esophagectomies often become hypothermic which may promote complications. We tested the hypothesis that aggressive warming to a core temperature of 37°C reduces postoperative pulmonary complications (PPCs) in elderly patients having esophageal cancer resections. Methods This study was a pre-defined sub-study of a multi-center, parallel group, superiority trial (PROTECT). Patients aged >65 years and having elective radical resection of esophageal cancer in a single center were randomly allocated into either aggressive warming group (target intraoperative core temperatures of 37°C) or routine thermal management group (target intraoperative core temperatures of 35.5°C). The primary endpoint was the incidence of PPCs. Secondary endpoints included duration of chest tube drainage and other postoperative complications. Results A total of 300 patients were included in the primary analysis. PPCs occurred in 27 (18%) of 150 patients in the aggressive warming group and 31 (21%) of 150 patients in the routine thermal management group. The relative risk (RR) of aggressive versus routine thermal management was 0.9 (95% CI: 0.5, 1.4; P=0.56). The duration of chest drainage in patients assigned to aggressive warming was shorter than that assigned to routine thermal management: 4 [3, 5] days vs. 5 [4, 7] days; hazard ratio (HR) 1.4 [95% CI: 1.1, 1.7]; P = 0.001. Fewer aggressively warmed patients needed chest drainage for more than 5 days: 30/150 (20%) vs. 51/150 (34%); RR:0.6 (95% CI: 0.4, 0.9; P=0.03). The incidence of other postoperative complications were similar between the two groups. Conclusions Aggressive warming does not reduce the incidence of PPCs in elderly patients receiving esophagectomy. The duration of chest drainage was reduced by aggressive warming. But as a secondary analysis of a planned sub-group study, these results should be considered exploratory. Clinical trial number and registry URL: http://www.chictr.org.cn/showproj.aspx?proj=37099 (ChiCTR1900022257)